Weird but true! : Canada : 300 outrageous facts about the True North. - National Geographic Society (U.S.) (Washington, D.C. : National Geographic, 2018)
Collects three hundred facts about Canada's wildlife, cuisine, history, sports, and culture.
Includes index.
Keywords: Canada -- Miscellanea -- Juvenile literature; Canada -- Juvenile literature; Canada -- Miscellanea